2017
DOI: 10.1108/he-08-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of New Zealand-based children in consuming fruits and vegetables

Abstract: Purpose It is known that the consumption of fruits and vegetables in children is declining despite wide-spread national and international policy attempts to increase consumption. The purpose of this paper is to investigate the experiences of children’s consumption of fruits and vegetables so as to facilitate better health education targeting. Design/methodology/approach In this qualitative descriptive exploratory study, peer group interviews were undertaken with 18 girls and 18 boys, aged 8-11, from schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In addition, the children in this study demonstrated a higher preference for fruits as compared to vegetables. This finding is supported by Dresler et al ( 30 ), which reported that children preferred mild and sweet vegetables such as carrots, corns, potatoes, broccolis and cauliflowers. This factor may also influence the children’s preferences in consuming more fruits compared to vegetables owing to the bitter taste of vegetables ( 17 ).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, the children in this study demonstrated a higher preference for fruits as compared to vegetables. This finding is supported by Dresler et al ( 30 ), which reported that children preferred mild and sweet vegetables such as carrots, corns, potatoes, broccolis and cauliflowers. This factor may also influence the children’s preferences in consuming more fruits compared to vegetables owing to the bitter taste of vegetables ( 17 ).…”
Section: Discussionsupporting
confidence: 64%
“…The use of fun, creative, and experiential learning was found to positively influence children’s attitude to F&V. This supports our previous work that found attitude was a key driver of F&V consumption among WA children [ 28 ]. In their study of children in rural New Zealand, Dresler et al recommended child-focused F&V campaigns should utilize the compelling techniques that are used by large companies to emphasise fun, energy, and colour of the produce [ 41 ]. In addition, cartoons depicting characters choosing healthy food have demonstrated a shift in children’s food choices to healthier options [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many children have been reported to possess limited food literacy skills, including poor awareness of what constitutes healthy food choices and limited preparation skills. School programs should be linked with the curriculum, utilise media [ 41 ], and include experiential learning to enhance skills [ 28 ]. The development and possession of food skills among children and adolescents translates to favourable health behaviours, and thus, improved dietary quality [ 52 ] and has been shown to decrease children’s requests for energy dense nutrient poor foods, which contribute to obesity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…By the age of 6 years, environmental factors that influence children's decision making are already set (101) . Both international (101,102) and New Zealand (103) studies have found that children do have good knowledge about the general healthiness of foods and are able to identify fruits and vegetables as being healthier compared with packaged food items such as chips (crisps) and sweets. Knowledge of healthy foods does not necessarily influence food preferences; this was highlighted in New Zealand, where children from the Manawatu Region were asked to construct a 'healthy' lunchbox and then construct their 'dream' lunchbox (104) .…”
Section: Socio-cultural Environmentmentioning
confidence: 99%